2015
DOI: 10.1038/cmi.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

The breast tumor microenvironment alters the phenotype and function of natural killer cells

Abstract: Natural killer (NK) cells are innate immune cells with the ability to identify and eliminate transformed cells. However, within tumors, many studies have described NK cells as non-functional. The developmental stage of tumor-associated NK cells and how this may relate to functionality has not been explored. We examined the developmental state of NK cells from polyoma middle T antigen (pyMT) transgenic mouse (MMTV-pMT) breast tumors. In pyMT tumors, NK cells were immature as evidenced by their decreased express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 38 publications
5
49
0
Order By: Relevance
“…Indeed, in our study, NK cell deficiency completely abolished the IL‐33‐mediated inhibition of tumor development in 4T1‐bearing mice, but not B16‐F10‐bearing mice. Besides, the heterogeneity of the TME also affects the antitumor immune response . Metastatic tumors are more sensitive to NK cells than CD8 + T cells, in contrast to primary tumors, in line with our observations in the 4T1 metastasis model.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, in our study, NK cell deficiency completely abolished the IL‐33‐mediated inhibition of tumor development in 4T1‐bearing mice, but not B16‐F10‐bearing mice. Besides, the heterogeneity of the TME also affects the antitumor immune response . Metastatic tumors are more sensitive to NK cells than CD8 + T cells, in contrast to primary tumors, in line with our observations in the 4T1 metastasis model.…”
Section: Discussionsupporting
confidence: 88%
“…In NK cells, the greater the alloreactivity between donor and recipient is, the better the antitumor efficacy is [13][14][15][16]. This relationship is consistent with the mechanisms of NK-cell recognition, whereby autologous NK cells are potentially inhibited by self MHC class-I molecules on cancer cells.…”
Section: Adoptive Cell Transfer (Act)supporting
confidence: 63%
“…For example, high infiltration of TAM in the tumours correlates with low number of interferon‐ γ ‐expressing active NK cells in human hepatocellular carcinoma and TAM from the tumour reduce activation and survival of NK cells . It is also reported that TAM isolated from the PyMT mouse mammary tumours significantly reduces cytotoxicity of NK cells in vitro . These results suggest that TAM depletion by blocking TAM recruitment or survival signals (e.g.…”
Section: Tam Targeting For Adoptive Ctl Transfer Therapymentioning
confidence: 91%